1998
DOI: 10.1007/pl00007035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Putrescine, 4-PU-30, and Abscisic Acid on Maize Plants Grown under Normal, Drought, and Rewatering Conditions

Abstract: The experiments were carried out with maize (Zea mays L.) seedlings, hybrid Kneja 530, grown hydroponically in a growth chamber. Twelve-day-old plants were foliar treated with putrescine, N1-(2-chloro-4-pyridyl)-N2-phenylurea (4-PU-30), and abscisic acid (ABA) at concentrations of 10(-5) m. Twenty-four hours later the plants were subjected to a water deficit program, induced by 15% polyethylene glycol (PEG; molecular weight, 6,000). Three days after drought stress half of the plants were transferred to nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The rate of transpiration depends not only on the influence of the stomata, but also on leaf water content and other factors (Ghannoum et al, 2003). Todorov et al (1998) also found a higher rate of transpiration in maize plants treated with ABA under drought condition. Coronatine might have regulated the stomatal conductivity to reduce leaf water consumption under drought stress as reported for ABA (Schroeder et al, 2001;Luan, 2002) and JA or methyl jasmonate (MeJA) (Lan et al, 2004), but this remains to be examined further.…”
Section: Discussionmentioning
confidence: 81%
“…The rate of transpiration depends not only on the influence of the stomata, but also on leaf water content and other factors (Ghannoum et al, 2003). Todorov et al (1998) also found a higher rate of transpiration in maize plants treated with ABA under drought condition. Coronatine might have regulated the stomatal conductivity to reduce leaf water consumption under drought stress as reported for ABA (Schroeder et al, 2001;Luan, 2002) and JA or methyl jasmonate (MeJA) (Lan et al, 2004), but this remains to be examined further.…”
Section: Discussionmentioning
confidence: 81%
“…Phagocytosis activity and ROS production in HKLs were concomitantly enhanced during oxidative burst throughout the experiment, which suggests that an enhanced leucocyte microbe-killing capacity is a key factor in increased resistance to disease. These regulations may be attributed to the potential effect of putrescine, which acts as radical scavenger [31]. Bekheta and El-Bassiouny [32] found that foliar application of putrescine in wheat plants decreased peroxidase and polyphenol oxidase, and increased catalase and superoxide dismutase activities.…”
Section: Discussionmentioning
confidence: 99%
“…All naturally polyamines including spermidine, spermine, codavarine and putrescine strongly inhibited opening of stomata (Liu-Kun et al, 2000). Some of the results are well documented as on chickpea under salinity (Dhingra et al, 1997), maize under drought (Todorov-D et al, 1998) and on groundnut seedling (Vakharia et al, 2003), which suggest the possibility of foliar application of putrescine to mitigate the effect of water stress. In legumes, moisture stress has drastic effects on nitrogen fixation besides plant growth (Sinclair et al, 1987 andSerraj et al, 1999).…”
Section: Introductionmentioning
confidence: 91%